2011
DOI: 10.1371/journal.pone.0024665
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Chemoresistance in Gliomas Is Associated with Increased Mitochondrial Coupling and Decreased ROS Production

Abstract: Temozolomide (TMZ) is an alkylating agent used for treating gliomas. Chemoresistance is a severe limitation to TMZ therapy; there is a critical need to understand the underlying mechanisms that determine tumor response to TMZ. We recently reported that chemoresistance to TMZ is related to a remodeling of the entire electron transport chain, with significant increases in the activity of complexes II/III and cytochrome c oxidase (CcO). Moreover, pharmacologic and genetic manipulation of CcO reverses chemoresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
131
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 49 publications
8
131
0
7
Order By: Relevance
“…1). Corroborating previous studies, cell groups with increased levels of ROS exhibited a lower cell viability than those with reduced ROS levels (33,34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…1). Corroborating previous studies, cell groups with increased levels of ROS exhibited a lower cell viability than those with reduced ROS levels (33,34).…”
Section: Discussionsupporting
confidence: 82%
“…TMZ also reduces the membrane potential of the mitochondrion, releases cytochrome c from this organelle, and increases activated caspases 3 and 9 cell content (32). Oliva et al (2011) suggested that U251MG cells demonstrated an increase in ROS production at 2 and 4 h post-TMZ (33), which indicated that oxidative stress contributed to the TMZ effects on astrocytoma tumor cells, as confirmed by a protective effect obtained with the antioxidant N-acetylcysteine. Indeed, TMZ at 300 µM caused a 10-fold increase in ROS levels in TMZ-sensitive U251MG cells, but no effect occurred on resistant cells (33).…”
Section: Discussionmentioning
confidence: 96%
“…Aichler et al (18) reported that knockdown of MT-CO7A2 with siRNA increased chemosensitivity after chemotherapy with cisplatin and 5-flurouracil in esophageal adenocarcinoma cells. Oliva et al (19,20) revealed that pharmacologic and genetic manipulation of cytochrome c oxidase restored chemosensitivity in chemoresistant glioma cells. From these and our results, cytochrome c oxidase seems to be a significant gene which induces chemo or radioresistance, and it may be a target gene for treatment to improve chemo or radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, although the BBB may be disrupted at the tumor core, it is intact at other tumor areas where the presence of tight junctions and transporter proteins of the ABC family prevents access of chemotherapeutics drugs to tumor cells. The alkylating agent temozolomide (TMZ), the front-line drug used for GBM treatment induces mitochondria uncoupling, ROS production, DNA strand breaks in GBM cells [10,11] and show a modest increase in patents survival rate [6]. However, a great number of patients with recurrent GBM develop resistance to the second cycle of TMZ and the treatment Chemotherapy : Open Access efficacy is further decreased.…”
Section: Glioblastoma Multiformementioning
confidence: 99%
“…However, a great number of patients with recurrent GBM develop resistance to the second cycle of TMZ and the treatment Chemotherapy : Open Access efficacy is further decreased. Expression of ATP-dependent drug efflux pumps, increase in mitochondria function and decrease of ROS production are just some of the mechanisms responsible for TMZ resistance [11,12].…”
Section: Glioblastoma Multiformementioning
confidence: 99%